BRAIN VOLUME CHANGE AND DISABILITY IN FINGOLIMOD TRIALS. Issue 10 (9th September 2014) - Nicholas, Richard; Barkhof, Frederik; Cohen, Jeffrey; Radue, Ernst-Willhelm; Kappos, Ludwig; Häring, Dieter; Sfikas, Nikolaos; von Rosenstiel, Philipp; Francis, Gordon
Abstract : Objective: Investigate relationships between Brain Volume (BV) loss and clinical and MRI outcomes observed in three phase 3 fingolimod trials. Method: Percentage BV change (PBVC) was measured in the core-phases and extensions of FREEDOMS, FREEDOMS II and TRANSFORMS using 'Structural Image Evaluation Normalization, of Atrophy'. During the core-phases, correlations were assessed between PBVC and: cumulative Gd+-lesion count (LC); T2-lesion volume change (LVC);new/enlarging T2-LC; T1-hypointense LVC; number of confirmed relapses; EDSS score change; and MSFC score change. Proportions of patients with 3- or 6-month confirmed disability progression (CDP) and correlations between PBVC and EDSS were determined. Results: In FREEDOMS, FREEDOMS II and TRANSFORMS, PBVC consistently correlated best with cumulative Gd+-LC(p<0.0001), new/enlarging T2-LC (p<0.0001) and number of confirmed relapses (p<0.005). PBVC correlated with EDSS and MSFC in FREEDOMS (p<0.001), and with MSFC in FREEDOMS II (p=0.016). In combined study data PBVC correlation with EDSS strengthened over time (month 48, p=0.0001). Stronger correlation was seen in patients with 3- or 6-month CDP (month 48, p<0.0001). Conclusion: BV loss was greatest in patients who relapsed or who developed new Gd+ or T2-lesions. By reducing BV loss, fingolimod may slow disability progression.